Aging‐related hyperphosphatemia impairs myogenic differentiation and enhances fibrosis in skeletal muscle. Issue 5 (1st August 2021) - Sosa, Patricia; Alcalde‐Estévez, Elena; Asenjo‐Bueno, Ana; Plaza, Patricia; Carrillo‐López, Natalia; Olmos, Gemma; López‐Ongil, Susana; Ruiz‐Torres, María Piedad
Abstract: Background: Hyperphosphatemia has been related to the development of sarcopenia in aging mice. We describe the intracellular mechanisms involved in the impairment of the myogenic differentiation promoted by hyperphosphatemia and analyse these mechanisms in the muscle from older mice. Methods: C2 C12 cells were grown in 2% horse serum in order to promote myogenic differentiation, in the presence or absence of 10 mM beta‐glycerophosphate (BGP) for 7 days. Troponin T, paired box 7 (Pax‐7), myogenic factor 5 (Myf5), myogenic differentiation 1 (MyoD), myogenin (MyoG), myocyte enhancer factor 2 (MEF2C), P300/CBP‐associated factor (PCAF), histone deacetylase 1 (HDAC1), fibronectin, vimentin, and collagen I were analysed at 48, 72, and 168 h, by western blotting or by immunofluorescence staining visualized by confocal microscopy. Studies in mice were performed in 5‐ and 24‐month‐old C57BL6 mice. Three months before sacrifice, 21‐month‐old mice were fed with a standard diet or a low phosphate diet, containing 0.6% or 0.2% phosphate, respectively. Serum phosphate concentration was assessed by a colorimetric method and forelimb strength by a grip test. Fibrosis was observed in the tibialis anterior muscle by Sirius Red staining. In gastrocnemius muscle, MyoG, MEF2C, and fibronectin expressions were analysed by western blotting. Results: Cells differentiated in the presence of BGP showed near five times less expression of troponin T and kept higher levels of Pax‐7 than control cells indicating a reduced myogenic differentiation. BGP reduced Myf5 about 50% and diminished MyoD transcriptional activity by increasing the expression of HDAC1 and reducing the expression of PCAF. Consequently, BGP reduced to 50% the expression of MyoG and MEF2C. A significant increase in the expression of fibrosis markers as collagen I, vimentin, and fibronectin was found in cells treated with BGP. In mice, serum phosphate (17.24 ± 0.77 mg/dL young; 23.23 ± 0.81 mg/dL old; 19.09 ± 0.75 mg/dL old with low phosphate diet) correlates negatively ( r = −0.515, P = 0.001) with the muscular strength (3.13 ± 0.07 gf/g young; 1.70 ± 0.12 gf/g old; 2.10 ± 0.09 gf/g old with low phosphate diet) and with the expression of MyoG ( r = −0.535, P = 0.007) and positively with the expression of fibronectin ( r = 0.503, P = 0.001) in gastrocnemius muscle. The tibialis anterior muscle from old mice showed muscular fibrosis. Older mice fed with a low phosphate diet showed improved muscular parameters relative to control mice of similar age. Conclusions: Hyperphosphatemia impairs myogenic differentiation, by inhibiting the transcriptional activity of MyoD, and enhances the expression of fibrotic genes in cultured myoblasts. Experiments carried out in older mice demonstrate a close relationship between age‐related hyperphosphatemia and the decrease in the expression of myogenic factors and the increase in factors related to muscle fibrosis.